Experience of Community Learning Activity Centers (PKBM) in Facilitating Lifelong Learning in Communities - Sulaeman, Devi; Kamil, Mustofa; Sudrajat Ardiwinata, Jajat; Saepudin, Asep (PT. Multidisciplinary Press Indonesia, 2024)
This research is motivated by the fact that to facilitate lifelong learning in society, PKBM needs to carry out instructional planning or design, namely analyzing community needs, designing learning programs; develop strategy materials and various learning resources; implement materials, learning methods, and various learning resources in the learning process; and carry out regular evaluations. The aim of this research is to determine and analyze the experience of community learning activity centers (PKBM) in facilitating lifelong learning communities. This research uses qualitative research with field research methods. The results of this research show that in creating a lifelong learning society, learning resources are needed that facilitate the learning process. Apart from that, learning resources in the community are also needed to provide learning opportunities for the entire community. This is in accordance with the 9-year compulsory education program launched by the Government. PKBM is one way that can facilitate learning to improve community performance.